Enhancing Innovation in Higher Education through Artificial Intelligence and Intellectual Property - Barqawi, Laila; Al-Arasi, Sarah; Abdallah, Mohammad; Numan, Bernadette Hanna; Al-Afaishat, Muneer Mohammad Shada (Journal of Ecohumanism, 2024)
The integration of artificial intelligence (AI) and Intellectual Property (IP) within academic settings is rapidly advancing, with the potential to drive innovation and entrepreneurship. This study aims to explore how AI and IP rights can be utilized in higher education to support entrepreneurial activities among university students. The central hypothesis is that combining AI-driven tools with a well-structured IP framework can significantly improve the environment for innovation in universities, leading to greater student involvement in entrepreneurial efforts. Initial findings suggest that AI-driven tools, such as patent analysis software and market research algorithms, can make IP management more efficient and help identify innovations with commercial potential. Furthermore, universities with effective IP policies and support systems have demonstrated higher levels of student participation in entrepreneurial initiatives. In conclusion, incorporating AI and IP rights into the academic context encourages a culture of innovation and entrepreneurship among students. By offering the necessary tools and legal structures, universities can create an atmosphere that motivates students to engage in entrepreneurial ventures, ultimately contributing to economic growth and enhancing global competitiveness.